(untitled) (Nativa, 2025)
In this research, the richness, diversity and similarity of bird species were evaluated in six fragments of tropical forests from 170 to 2100 meters above sea level in the western Andes, central Ecuador. The bird count was carried out in 2019 using the technique of counting birds by points, in the forest fragments: Las Cascadas, Ñungañan, Jardín de los Sueños, Los Laureles, Machay, and La Esperanza. The ecological parameters were evaluated by the Shannon Index, relative abundance, and Sorensen Index. The difference between forest fragments and ecological parameters was analyzed using the non-parametric statistical technique of Kruskal-Wallis (p<0.05) and comparison by post hoc. The comparison of the forest fragments was determined with the Mann-Whitney test, because the assumption of normality according to the Shapiro-Wilk test for the analysis of variance was not met. The results showed 219 species of birds belonging to 70 genera, 48 families, and 9 orders. The families with the highest wealth were Thraupidae (15.3%), Tyrannidae (12.7%), Fringillidae (5.4%), and Accipitridae (1.4%). The highest relative abundance of birds for La Esperanza was the species: Anisognathus somptuosus and Streptoprocne rutila; Ñungañan: Pygochelidon cyanoleuca and Coragyps atratus; Los Laureles: Thraupis episcopus and Bubulcus ibis; Machay: Egretta thula and Arremon aurantiirostris; and Las Cascadas: Thraupis episcopus and Forpus coelestis. For the components of bird species diversity in the six forest fragments, there are significant variations in species richness, abundance, and similarity (p<0.05); La Esperanza and Ñungañan being the least disturbed fragments, which presented a greater diversity of species and abundance of birds. These results highlight the importance of these forest fragments as refuges for bird biodiversity, despite the anthropogenic pressures they face. Keywords: bird counting; forest fragment; habitat loss; relative abundance. Espécies de aves em fragmentos de florestas tropicais, em diferentes cotas altitudinais, dos Andes ocidentais do Equador RESUMO: Nesta pesquisa foi avaliada a riqueza, diversidade e similaridade de espécies de em seis fragmentos de florestas tropicais entre 170 a 2100 metros acima do nível do mar, na região ocidental dos Andes, centro do Equador. A contagem de aves foi realizada em 2019 pela técnica de contagem pontual de aves, nos seguintes fragmentos de floresta: Las Cascadas, Ñungañan, Jardín de los Sueños, Los Laureles, Machay e La Esperanza. A avaliação dos parâmetros ecológicos foi realizada utilizando o índice de Shannon, abundância relativa e índice de Sorensen. A diferença entre fragmentos florestais e parâmetros ecológicos foi analisada pela técnica estatística não paramétrica de Kruskal Wallis (p<0,05) e comparação post hoc por meio do teste de Mann Whitney. Para a comparação dos fragmentos florestais, eles foram determinados pelo teste isso porque o pressuposto de normalidade não foi atendido pelo teste de Shapiro Wilks para análise de variância. Os resultados mostraram 219 espécies de aves pertencentes a 70 gêneros, 48 famílias e 9 ordens. As famílias com maior riqueza foram Thraupidae (15,3%), Tyrannidae (12,7%), Fringillidae (5,4%) e Accipitridae (1,4%). As maiores abundâncias relativas de aves para La Esperanza foram as espécies: Anisognathus somptuoso e Streptoprocne rutila; Ñungañan: Pygochelidon cianoleuca e Coragyps atrato; Los Laureles: Thraupis episcopus e Bubulcus ibis; Machay: Egreta Thula e Arremon aurantiirostris e Las Cascadas: Thraupis episcopus e Forpus coelestis. Para os componentes da diversidade de espécies de aves nos seis fragmentos florestais, há variações significativas na riqueza, abundância e similaridade de espécies (p<0,05). Utilizando as espécies como bioindicadoras é possível inferir que La Esperanza e Ñungañan foram os fragmentos menos perturbados e apresentaram maior diversidade e abundância de aves. Estes resultados destacam a importância destes fragmentos florestais como refúgios para a biodiversidade de aves, apesar das pressões antrópicas que enfrentam. Palavras-chave: contagem de aves; fragmento florestal; perda de habitat; abundância relativa.